2006
DOI: 10.1111/j.1478-3231.2005.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin non‐selectively induces apoptosis in fibrotic and normal livers

Abstract: This study indicates that the apoptosis-inducing strategy to treat liver fibrosis has high potential, but it will be necessary to develop an HSC-specific therapy to prevent adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 22 publications
7
41
2
Order By: Relevance
“…However, the activation does not seem to be complete as preincubation of the cells with endotoxin further sensitized Kupffer cells to gliotoxin-induced death. These observations contrast a recent study reporting comparable gliotoxin-induced apoptosis of Kupffer cells and HSCs in normal and cirrhotic livers (54). The reason for this discrepancy may be that liver slices were incubated for 8h with gliotoxin in vitro (54), while we and others (1,24) investigated the effect of gliotoxin in vivo.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the activation does not seem to be complete as preincubation of the cells with endotoxin further sensitized Kupffer cells to gliotoxin-induced death. These observations contrast a recent study reporting comparable gliotoxin-induced apoptosis of Kupffer cells and HSCs in normal and cirrhotic livers (54). The reason for this discrepancy may be that liver slices were incubated for 8h with gliotoxin in vitro (54), while we and others (1,24) investigated the effect of gliotoxin in vivo.…”
Section: Discussioncontrasting
confidence: 53%
“…Although the mechanism by which gliotoxin exhibits its toxic effects is not clear, a number of studies using commercially produced gliotoxin or crude culture filtrates have shown that exposure can have profound immunosuppressive effects on different mammalian cell types: for example, gliotoxin induces death by apoptosis in neutrophils (42), macrophages (43), and human hepatocytes (16). Gliotoxin also appears to have immunomodulatory effects on human monocytes (18), mast cells (27), and T lymphocytes (37).…”
Section: Discussionmentioning
confidence: 99%
“…With continued refinements, however, liver slices again offer some unique advantages (664,668) and have more recently been used to test drug targeting methods (410,411), antifibrotic therapies (224), and cell fate during injury and repair following exposure to hepatotoxins (221). The slice technology can be complemented with either real-time PCR for stellate cell-specific genes (665) or laser-capture microdissection to enrich for stellate cells recovered from within the slice.…”
Section: Other Models: Liver Slices In Vivo Methodsmentioning
confidence: 99%